Numerical Simulation of Dynamic Response of Submerged Floating Tunnel under Regular Wave Conditions - Wenlong Luo; Bo Huang; Yao Tang; Hao Ding; Ke Li; Liang Cheng; Qingyang Ren (Shock and Vibration)
A submerged floating tunnel (SFT) is considered an innovative alternative to conventional bridges and underground or immersed tunnels for passing through deep water. Assessment of hydrodynamic performance of SFT under regular wave loading is one of the important factors in the design of SFT structure. In this paper, a theoretical hydrodynamic model is developed to describe the coupled dynamic response of an SFT and mooring lines under regular waves. In this model, wave-induced hydrodynamic loads are estimated by the Morison equation for a moving object, and the simplified governing differential equation of the tunnel with mooring cables is solved using the fourth-order Runge–Kutta and Adams numerical method. The numerical results are successfully validated by direct comparison against published experimental data. On this basis, the effects of the parameters such as the cable length, buoyancy-weight ratio, wave period, wave steepness, and water/submergence depth on the dynamic response of the SFT under wave loading are studied. The results show that tunnel motions and cable tensions grow with wave height and period and decrease with submergence depth. The resonance of the tunnel will be triggered when the wave period is close to its natural vibration period, and the estimation formula of wave period corresponding to tunnel resonance is proposed in this paper.